ANALISIS PENGARUH INTELLECTUAL CAPITAL DENGAN IB- TERHADAP TINGKAT KESEHATAN BANK UMUM SYARIAH DENGAN METODE PENILAIAN RGEC PERIODE 2011-2015 - FIKASARI, RIFKI (Jurnal Akuntansi AKUNESA, 2016)
Abstract The purpose of this study is to investigate the effect of intellectual capital with iB-(Islamic Banking Value Added Intellectual Capital) on the bank health with measurement method by RGEC (Risk Profile, Good Corporate Governance, Earning, Capital). This study is quantitative research and used secondary data from annual report y of Indonesian Islamic bank for 2011-2015 period. The sampling technique used purposive sampling which obtained 9 Islamic Banks and the data used as many as 45 data. The data analysis technique is Partial Least Square (PLS). The finding show that intellectual capital with iB- influences positively to the bank health with measurement method by RGEC. For the most significant indicator for intellectual capital  (iB- and bank health are Value Added Capital Employed (VACA) and Return on Asset (ROA)  Keywords: Intellectual Capital, iB-Bank Health, RGEC